Analisis Peran Dinas Koperasi Usaha Kecil Menengah Kota Medan Terhadap Perkembangan UMKM Di Kota Medan - Nanda Aulia; Juliana Nasution (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
The Cooperative Service is one of the government's extensions to be able to develop MSMEs and improve MSME business development which originally had the characteristics of an informal business to a formal business. The method used in this research is qualitative method. However, some of the main problems that are very often faced by MSME entrepreneurs are the lack of capital so that the lack of business development for MSME entrepreneurs requires the role of the Small and Medium Business Cooperative Service. Several alternative financing encourage MSMEs to be able to access financial institutions in particular so that it is hoped that business actors will no longer experience difficulties in carrying out their business activities. One of the financing sectors that can be the answer to problematic financing for MSMEs, one of which is the role of cooperatives that contribute to the continuity of MSME businesses so that cooperatives can support the MSME financing sector and are able to synergize so that they can support the national economy and support the economy of each region.Keyword :        The Role of the Cooperative Service, Small and Medium Enterprises, MSME Development, Medan City